Assessing the Correlation between the Socioeconomic Level and Cognitive Function among Older Adults in Egypt - AbouGabal, Macy (AUC Knowledge Fountain, 2023)
The number of older adults is increasing worldwide at an unprecedented rate. Some countries began to understand the challenges of aging, while others are still at the stage of comprehending the true dimensions of the situation. There is a global focus on aging research to appropriately mitigate the negative impact of aging and cognitive decline. Not only that dementia add economic pressure on governments, it also increase the psychological and physical burden of the caregivers. Scholars have previously studied socioeconomic level in three variables, namely work, education, and income, and their relationship with cognitive function. It was concluded that the work environment has a role in shaping the cognitive trajectory of the individual. Work-related stress is induced by low level of job control and high level of job demands, which reduces hippocampal activity, and fastens the aging process. On another hand, education increases the cognitive reserve that in turn stimulates brain activity and promote healthy aging. Other studies argued that personal income does not only affect the aspect of treatment affordability but also the mental health aspect of the individual. Although the majority of dementia cases reside in Low- and Middle Income countries, there are few accurate representative data for the situation. For this reason, this pilot study aims to contribute to and identify the correlation between the socioeconomic level and the cognitive performance of the aging population in Egypt. In this pilot study, data from 122 participants were collected on the course of two months, 118 of whom were included in the analysis. Although it is a pilot study, results still provided some valuable findings that would direct future scientific studies, and suggestions were provided as policy alternatives.